Antennal Lobe Atlas of an Emerging Corn Pest, Athetis dissimilis - Dong, Jun-Feng; Jiang, Nan-Ji; Zhao, Xin-Cheng; Tang, Rui (Frontiers in Neuroanatomy, 2020)
Moths develop sophisticated olfactory systems to sense the airborne chemical cues from the environment. Understanding the structural basis in the neuronal centre is a fundamental neuroethological step. As an emerging crop pest, little is known about Athetis dissimilis on its morphology or on its neuronal organizations. Through the antibody staining and digital 3D modelling, we re-constructed the primary olfactory centre - the antennal lobe of A. dissimilis. Respective 68.8 + 3.1 male glomeruli and 70.8 + 1.0 female glomeruli in the antennal lobes were identified with obvious sexual dimorphism. In special, male adults of A. dissimilis contain a macro glomerular complex which consists of three subunits, while female lobe has four relatively enlarged glomeruli at the entrance of the antennal nerve. Glomeruli were later clustered with deviation and variance, and referring to reported olfactory related receptor family genes in 7 different moth species, we found that glomerular counts of these insects are better related to sum of odorant receptor and ionotropic receptor numbers, suggesting ORs and IRs may both involved in olfaction of Noctuidae moths.